Sistemas avançados em iluminação natural: análise da influência da configuração urbana na aplicação do painel de corte a laser em Maceió - Ribeiro, Pedro Vitor Sousa (2017)
The use of elements that help the project designer to make the environments more comfortable and efficient comes from an analysis that identifies the best solutions for each reality. Studies show that the use of light redirection panels in side openings reduces the incidence of direct sunlight in the area near the window, increases diffuse light in the first third of the room closest to the window, and improves the overall distribution of light in the room. The present work studies the laser cut panel application in an urban verticalization scenario in Maceió. The methodology used is divided into two parts: the first one consists in the elaboration of an additional algorithm for the TropLux software that allows to simulate computationally the material chosen, and it’s performance was verified after a comparison of the reflectance and transmittance directional obtained, and the values found in literature; The second part aims to analyze the advanced element utilization in an denser urban environment using the developed algorithm, in which the models were analyzed using parameters of average illuminance and it’s uniformity, as well as the statistics analysis of the data. The validation carried out indicates that the operation of the module corresponds to other results obtained in literature, attesting its effectiveness. The urban models analysis results indicate that the panel positioned vertically, at 0 °, works well as sunscreen against the direct rays of the sun. For light redirection function the element presented better results for clear skies partially covered when applied at 30°, and at 45° of inclination for clear skies, independent of the urban canyon orientation. However, scenarios of reduced vision of sky, less than 20%, presented different behavior, this need complementary analysis.